Low‐Density Crystals in Charged Colloids: Comparison with Yukawa Theory. Issue 2 (23rd January 2015) - Rios de Anda, I.; Statt, A.; Turci, F.; Royall, C.P.
Abstract: Charged colloids can behave as Yukawa systems, with similar phase behaviour. Using particle‐resolved studies, we consider a system with an unusually long Debye screening length which forms crystals at low colloid volume fraction φ ≈ 0.01. We quantitatively compare this system with the Yukawa model and find that its freezing point is compatible with the theoretical prediction but that the crystal polymorph is not always that expected. In particular we find body‐centred cubic crystals where face‐centred cubic crystals are expected. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)